If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24 + -2x = -4x + 4 Reorder the terms: 24 + -2x = 4 + -4x Solving 24 + -2x = 4 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 24 + -2x + 4x = 4 + -4x + 4x Combine like terms: -2x + 4x = 2x 24 + 2x = 4 + -4x + 4x Combine like terms: -4x + 4x = 0 24 + 2x = 4 + 0 24 + 2x = 4 Add '-24' to each side of the equation. 24 + -24 + 2x = 4 + -24 Combine like terms: 24 + -24 = 0 0 + 2x = 4 + -24 2x = 4 + -24 Combine like terms: 4 + -24 = -20 2x = -20 Divide each side by '2'. x = -10 Simplifying x = -10
| 12x=3.99 | | -4/3v-9/5=-3/2 | | 12*8.50=x | | x^2+y^2+14x+30y+258=0 | | x+4*x-5=35 | | x+4*x-5=36 | | -11=4+5w | | 9*12x=16.20 | | 4x+5y-6z=24 | | x^2-16x+11=5 | | 3x^3=51 | | 24=8w | | 28-2x=-4x+4 | | 8x=6*4 | | 3y+1+6x-13+8x-61=180 | | 5(x-10)=2x+5 | | 6x=705 | | 2d-8=25 | | 5x-18=3x+56 | | 20=-10+5 | | 7/x-4=-3 | | 2N-10=-2 | | 5c+8=43 | | -12x=66 | | N-5=1 | | .3333333333(3x+6)=.5(x-4) | | 3/4f=-0.75 | | -5x+15=20x+10 | | 10x^2+53x+36= | | Tanh^-1(3/4) | | 6/7k=6/7 | | 3(x-2)^3/4 |